The Australian longitudinal study of health and relationships - Richters Juliet; Shelley Julia M; Pitts Marian K; Smith Anthony MA; Ferris Jason (BMC, 2007)
Abstract Background Ensuring the sexual and reproductive health of the population is essential for the wellbeing of a nation. At least three aspects of sexual and reproductive health are among the key policy issues for present Australian governments: maintaining and increasing the birth rate; reducing the abortion rate; and preventing and controlling Chlamydia infections. The overall aim of the Australian Longitudinal Study of Health and Relationships is to document the natural history of the sexual and reproductive health of the Australian adult population. Methods/design A nationally representative sample of Australian adults 16-64 years of age was selected in a two-phase process in 2004-2005. Eligible households were identified through random digit dialling. We used separate sampling frames for men and women; where there was more than one eligible person in a household the participant was selected randomly. Participants completed a computer-assisted telephone interview that typically took approximately 25 minutes to complete. The response rate was 56%. A total of 8,656 people were interviewed, of whom 95% (8243) agreed to be contacted again 12 months later. Of those, approximately 82% have been re-contacted and re-interviewed in 2006-07 (Wave Two), with 99% of those agreeing to be contacted again for Wave Three. Discussion ALSHR represents a significant advance for research on the linked topics of sexual and reproductive health. Its strengths include the large sample size, the inclusion of men as well as women, and the wide age range of the participants.